TEMPERATURA CORPÓREA DE NOVILHAS PANTANEIRA E GIROLANDO MANEJADAS NAS QUATRO ESTAÇÕES DO ANO - LIMA, P. G. L.; SALLA, L. E.; SANTOS, M. G. R.; SILVA, K. V.; ALVES, D. A.; OLIVEIRA, M. V. M. (ANAIS DO ENIC, 2016)
-